Huizu between Religious Control and Freedom in Communist China: A Study of Chinese Muslim Minority - Ayesha Qurrat ul Ain (Journal of Islamic and Religious Studies, 2018)
The freedom of religion in communist China is an ambiguous notion as the communist party understands religion as a reminiscent of backwardness and simultaneously proclaims the freedom of religion in the country. Islam, religion practiced by Hui minority, is included among the recognized religions of China and its adherents are granted rights to follow it. This paper argues that the Communist party has employed a disguised policy of controlling religious belief through establishing state controlled religious organizations and imparting freedom to practice religion. The slow and steady mind-making through these institutions train Hui youth to withdraw from their religion and to facilitate this withdrawal, the previously extant correlation between Hui ethnicity and religion (Islam) has been eliminated by the state and Hui ethnicity has nothing to do with religious affiliation anymore. The data for this research has been collected through ethnographic research upon the Hui community of Xi’an, employing unobtrusive observation as well as intensive interviewing.